Menguak Titik Lemah BLU: Dampak Pengendalian Internal terhadap Kinerja dan Akuntabilitas Publik - Firmansyah, Amrie (Polytechnic of State Finance STAN, 2024)
This study aims to identify the weaknesses in internal control at Public Service Agencies (BLU) and analyze their impact on financial performance and public accountability across various sectors, including health and education. Using a scoping review method, the study explores literature related to BLU financial management, focusing on receivables management, inventory recording, internal audit, and financial flexibility. The findings reveal that major weaknesses in receivables management, particularly in the health sector, contribute to financial deficits. Furthermore, weaknesses in inventory recording and the execution of internal audits were found across sectors, leading to operational inefficiencies and declining public accountability. The financial flexibility granted to BLU, while providing autonomy in financial management, can exacerbate issues if not accompanied by strong internal control systems. Therefore, strengthening internal controls, implementing stricter audits, and providing management training are essential to improve BLU’s financial performance and accountability. The government is advised to reinforce internal control regulations and enhance BLU managerial capacity through financial and risk management training. This study contributes to the literature on BLU management and offers policy recommendations to improve BLU efficiency and accountability in Indonesia.